The Effect Of Work-Life Balance On Performance Young Employees With Work Engagement Mediation In Himbara Banking Sector Of Palangka Raya City - Benedikta Sianipar; Rita Sarlawa; Rian Sidiq Prakoso; Nurlia Eka Damayanti (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study aims to analyze the influence of work-life balance on performance. young employees with work engagement as a mediating variable in the sector The Himbara Banking of Palangka Raya City. The study used a quantitative explanatory approach with a sample of 100 young employees from BNI, BTN, and BRI Banks. Data were analyzed using the PLS-SEM method. through SmartPLS 4. The results showed that work- life balance has a positive and significant effect on employee performance and work engagement. Work engagement also has a positive effect on employee performance and is able to mediate the relationship between work-life balance and employee performance. These findings demonstrate the importance of work-life balance in influencing employee engagement and performance.